Nonlinear Resonance Behavior in the Human Exposed to Whole-Body Vibration - Suzanne D. Smith (Shock and Vibration)
The driving-point impedance technique was applied to identify nonlinear resonance behavior in the human exposed to sinusoidal vibration between 3 and 20 Hz at three acceleration levels. Up to four regions of resonance were observed. A significant decline in the first and fourth resonance frequency and the disappearance of the second resonance peak occurred with a fivefold increase in the acceleration level. A proposed, base-excited five degree-of-freedom model, representing major dynamic structures in the human, proved highly successful in simulating the typical impedance responses. The model was used to quantify the variations in the mass, stiffness, and damping characteristics associated with changes in the acceleration level.